Clozapine-Induced Phototoxicity: An Unusual Side Effect of Atypical Antipsychotics - S. Al-Aojan; A. Al-Khalifah (Case Reports in Dermatological Medicine)
Introduction. Clozapine is a second-generation antipsychotic used for treatment-refractory schizophrenia. Photosensitivity is a major concern when prescribing typical antipsychotics, while atypical antipsychotics are thought to be less photosensitive. Case Report. We report a 27-year-old military personnel who developed a phototoxic drug reaction after using clozapine for schizophrenia. Conclusion. Recognition of rare but possible ability of atypical antipsychotics to cause photosensitivity is pertinent to patients care and proper counseling.